X-ray absorption fine structure of carboxyl and other adventitious moieties attached to copper-supported graphene. (January 2019) - Wahab, Hud; Mertins, Hans-Christoph; Timmers, Heiko; Frankcombe, Terry J.
Abstract: The electronic and topographical structure of vapour-deposited graphene on copper is known to deteriorate in ambient conditions with time. This appears in X-ray absorption spectra at the carbon 1s edge as a reduction of π*- and σ*-resonance intensities and as fine structures at energies between the resonances. Our Density Functional Theory calculations show that the intensity reduction is due to the wrinkling of the graphene sheet, which may also cause a hitherto unobserved splitting of the σ*-resonance. The structure between the resonances can be due to adventitious adsorbates either at grain boundaries or at the graphene surface. The location of adsorbates, such as carboxyl, can be distinguished through the degree of anisotropy of the absorption. The hydrogen and carboxyl adsorbates at the graphene surface correspond to effectively isotropic peaks in the absorption spectrum, since the receiving carbon atom in the graphene sheet adopts sp 3 hybridisation. In contrast, carboxyl groups at the edges of graphene grains are predicted to only cause the anisotropic absorption of photons. This informs the interpretation of an experimentally observed X-ray absorption peak at 288.3 eV, which often persists even after high-temperature vacuum-annealing of graphene and may be caused by adsorbates clustering at the basal plane. Graphical abstract: Image 1